Framing Pemberitaan Holywings Di Detik.Com - Suci Ayu Rhasmi Amartiya; Amin Sihabuddin; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The research carried out was entitled "Framing Holywings Reporting on detik.com". This research is based on the problem of the efforts of irresponsible parties in the name of Muhammad and Mary at a Holywings party which ended in a free alcohol party, the aim of which was to corner Islam as a form of marketing strategy for opening business premises. This is of course not justified and it must be known that there are elements of religious blasphemy in it. Next, the aim of the research is to find out the framing of Holywings news on detik.com and to find out the Holywings news message on detik.com. The research method is qualitative. Data collection techniques include documentation, observation and library research. The data analysis technique is issue selection and aspect highlighting. The results of the research are first, Holywings news framing at detik.com, namely framing analysis, journalists also need to pay attention to how this issue is explained, reported and perceived by the media and the wider public. Word choice, narrative framing, and presentation of information in news stories can influence how people understand and interpret these issues. Journalists must strive to avoid bias or unbalanced emphasis in conveying news, so as to provide an objective and accurate picture of the resolution of current problems. Second, the Holywings news message on detik.com is that the mass media has a very important role in conveying various social injustices and exposing cases of violations committed by Holywings, this is a form of the function of the press as a social control and information function. The conclusion at this time is that Detik.com plays its role in channeling public aspirations in defending truth and justice and providing emphasis that also influences and colors the political policies of the state, nation and religion.